Hubungan Iklim Organisasi dengan Motivasi Kerja Pegawai Dinas Pendidikan Pemuda dan Olahraga Kabupaten Solok - Ivona Yunita (Universitas Negeri Padang, 2013)
This research was backgrounded by a phenomenon was that educate found in the education department of youth and sports Solok is still a lack of employees motivation in the work. The aims of This study are to know about relationship of organizational climate with employee motivation in the education department of Solok. The study population are all employees of education department of youth and sports Solok totaling 73 people, and the sample in this study is 40 people who se were taken by using a proportional stratified random sampling technique. the research instrument was a questionnaire Likert Scale models. The results of the data analysis showed that: 1) motivation of employees in the education youth and sports Solok is in good categories (78.23%), 2), organizational climate of education youth and sports Solok is in good category (80,8%) and 3) there is a significant relationship between organizational climate and motivation of employees working in the education department of youth and sports Solok with t by 7.82 at the 99% confidence level.